Kepercayaan dalam Transaksi Digital: Pengaruh Persepsi Risiko dan Persepsi Keamanan terhadap Minat Pembelian NFT di Indonesia - Joshua, Melvin; Aritonang, Reikman (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of risk perception and security perception on the intention to purchase NFTs in Indonesia, with trust as a mediating variable and innovativeness as a moderating variable. This research employs a quantitative approach with an explanatory method. Data were collected through questionnaires distributed to respondents aged 18 to 40 years who have experience in NFT marketplace transactions. The sampling technique used purposive sampling with a total of 220 respondents. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with the latest version of SmartPLS software. The results show that security perception has a positive and significant effect on trust, while risk perception does not have a significant effect. Moreover, trust positively and significantly influences the intention to purchase NFTs. However, innovativeness does not moderate the relationship between risk perception and trust or between security perception and trust. These findings indicate that security perception is the primary factor in building user trust in NFT platforms, while risk perception and innovativeness do not have a significant impact. This study contributes theoretically to understanding the relationship between risk perception, security perception, and trust in the NFT market. Practically, these findings encourage NFT platform developers to enhance security systems and provide education to strengthen user trust and drive NFT adoption in Indonesia.